REFORMASI, TEORI EKONOMI, DAN KEMISKINAN - Mubyarto, Mubyarto (Journal of Indonesian Economy and Business, 2004)
For 25 years now, the Pancasila economic theory has experienced âprosperity anddepressionâ. In 1980âs when the economy was booming the Indonesian economists weredebating seriously on the merit and demerit of the theory. Now after the economy had beenhaving difficulties to recover from the severe monetary crisis, the debate become hotterbecause the conventional economic theory has again demonstrated its inability. Inconnection with the role of IMFâs economists in helping Indonesian economists to rescuethe crisis, various national debate took place. The authorâs brief meeting with MuhammadYunus, Bangladeshâs most prominent economist in Dacca reactivated our long timeconcern on the need of ânative economic theoryâ for Indonesia which we had calledEkonomi Pancasila.Key words : self employment, socio-economic theory, poverty, ekonomi rakyat